The hardest working man : how James Brown saved the soul of America - Sullivan, James, 1965 November 7- (Gotham Books, 2008)
The story of the night James Brown kept the peace in the wake of the assassination of Martin Luther King, Jr., and delivered hope with an immortal performance. In the hours after King's death, Brown's concert at Boston Garden was slated for cancellation as police geared up for riots. After Brown butted heads with the mayor, the show was allowed to go on--and his emotional, electric performance was broadcast live on local television. Though rioting erupted in more than a hundred U.S. cities that night, Boston remained quiet. Not only bringing to life that transforming show, author Sullivan also charts Brown's incredible rise from poverty to self-made millionaire, making this book both a tribute to an unforgettable concert and a rousing biography of a revolutionary musician.--From publisher description.